Bond strength between TiN coating and microstructural constituents of a high speed steel determined by first principle calculations. (1st January 2022) - Gsellmann, Matthias; Scheiber, Daniel; Klünsner, Thomas; Zálešák, Jakub; Zhang, Zaoli; Leitner, Harald; Mitterer, Christian; Ressel, Gerald; Romaner, Lorenz
Abstract: The adhesion of protective hard coatings to the substrate is one of the most important parameters that influence the performance of metal cutting tools. By a combination of high-resolution transmission electron microscopy and first principles modelling we determine the interface adhesion between a TiN hard coating and microstructural constituents of a high speed steel on an atomic level for the first time. Based on experimentally observed orientation relationships, multiple structures are studied for each interface and both interface cohesion and resistance to sliding are evaluated for MC and M6 C carbides as well as the martensitic matrix to TiN coating. We find that TiN coatings have high adhesion to MC carbides, while lower adhesion is present for M6 C and the martensitic matrix. Close agreement with experimental measurements validates this approach and suggests new strategies for developing steels with increased coating adhesion. Graphical abstract: Image, graphical abstract